Measurements of Higgs boson properties in the diphoton decay channel in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2018)
Measurements of Higgs boson properties in the H decay channel are reported. The analysis is based on data collected by the CMS experiment in proton-proton collisions at =13 TeV during the 2016 LHC running period, corresponding to an integrated luminosity of 35.9 fb(-1). Allowing the Higgs mass to float, the measurement yields a signal strength relative to the standard model prediction of 1.18-0.14+0.17=1.18-0.11+0.12(stat)-0.07+0.09(syst)-0.06+0.07(theo), which is largely insensitive to the exact Higgs mass around 125 GeV. Signal strengths associated with the different Higgs boson production mechanisms, couplings to bosons and fermions, and effective couplings to photons and gluons are also measured.
Keywords: Hadron-Hadron scattering (experiments); Higgs physics; Photon production; BROKEN SYMMETRIES; GAUGE; MASS